2005
DOI: 10.1073/pnas.0501895102
|View full text |Cite
|
Sign up to set email alerts
|

In vivo formation and repair of DNA double-strand breaks after computed tomography examinations

Abstract: Ionizing radiation can lead to a variety of deleterious effects in humans, most importantly to the induction of cancer. DNA doublestrand breaks (DSBs) are among the most significant genetic lesions introduced by ionizing radiation that can initiate carcinogenesis. We have enumerated ␥-H2AX foci as a measure for DSBs in lymphocytes from individuals undergoing computed tomography examination of the thorax and͞or the abdomen. The number of DSBs induced by computed tomography examination was found to depend linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
342
3
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 384 publications
(386 citation statements)
references
References 26 publications
27
342
3
10
Order By: Relevance
“…Recently, γH2AX foci analysis has become a widely used tool to quantify DSBs on a single cell level after IR (2). γH2AX foci numbers of 30-35 per Gy per G1 cell have been reported (3)(4)(5)(6)(7)(8) suggesting that there is a 1:1 correlation between γH2AX foci and DSBs after IR of nonreplicating cells. However, the precise DSB induction yields following irradiation can depend on a number of factors (see, eg, (9)) and, we show here, are critically dependent upon the surface upon which the cells are grown and irradiated.…”
Section: Dna Double-strand Breaks (Dsbs) Represent Important Lesions mentioning
confidence: 99%
“…Recently, γH2AX foci analysis has become a widely used tool to quantify DSBs on a single cell level after IR (2). γH2AX foci numbers of 30-35 per Gy per G1 cell have been reported (3)(4)(5)(6)(7)(8) suggesting that there is a 1:1 correlation between γH2AX foci and DSBs after IR of nonreplicating cells. However, the precise DSB induction yields following irradiation can depend on a number of factors (see, eg, (9)) and, we show here, are critically dependent upon the surface upon which the cells are grown and irradiated.…”
Section: Dna Double-strand Breaks (Dsbs) Represent Important Lesions mentioning
confidence: 99%
“…6 Biologic experiments have demonstrated that the number of DNA double-strand breaks is closely related to the applied dose. 3,7 Several techniques for CT dose reduction, maintaining image quality on a diagnostic level, became a hot topic in clinical research. [8][9][10][11] Automated attenuation-based tube current modulation or so-called automatic exposure control techniques are widely used.…”
mentioning
confidence: 99%
“…It is well known that some components of DNA are most sensitive to radiation and that repair mechanisms of the cell are often ineffective due to these irreversible damages [10,12]. Lö brich et al described radiation-induced damage to DNA and that aggregation of base damage can lead to cell death, mutations and even generation of cancer [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…During irradiation the cell cultures of the experimental groups were always maintained at 4°C using ice cooling [12].…”
Section: Cell Culturementioning
confidence: 99%